Model of Reconfigurable Steganographic System Using Blockchain Technology - E. V. Timoschenko; A. F. Razhkov (Цифровая трансформация)
An effective method for solving data security problems is proposed. A new approach to the design of steganographic system based on the three basic methods - the introduction of parts of a shared secret into images with the possibility of further extraction of secret information, authentication of parts of a secret, self-healing of this security system. Such a system provides a greater degree of protection and secure data storage. The Windows application implements the proposed steganographic model, has no analogues and meets all the requirements set for steganographic software.